Earth Ice Age Dynamics: A Bimodal Forcing Hypothesis - Lai, Zhongping; Xu, Yantian; Zheng, Peisong (Frontiers in Earth Science, 2021)
The earth has gone through multiple ice ages in the past million years. Understanding the ice age dynamics is crucial to paleoclimatic study, and is helpful for addressing future climate challenges. Though ice ages are paced by variations in earth’s orbit geometry, how various climatic system components on the earth respond to insolation forcing and interact with each other remains unclear. A prevailing view argues that the initial responses occur in the northern high latitudes. Nonetheless, this opinion is challenged by recent reports, such as the lead of climate change in the Southern Hemisphere (SH) relative to that in the Northern Hemisphere (NH), the southern control on Atlantic meridional overturning circulations (AMOC), and the potential significance of Southern Hemisphere (SH). Here we present a new proposal concerning the earth’s ice age dynamics: the bimodal forcing hypothesis (BFH). The essential assumption of this hypothesis is that for glacial-interglacial cycles, the cooling (glaciation) starts from the northern high latitudes, whereas the warming (deglaciations) starts from the SH. Particularly, the BFH emphasizes the significance of SH oceans in accumulating and transferring heat for deglaciations. We compiled 100 global paleotemperature records for validation. The BFH is consistent with most of these records, and provides a straightforward and comprehensible way to interpret ice age on Earth.